The Minimalist program : the nature and plausibility of Chomsky's biolinguistics - Al-Mutairi, Fahad Rashed, 1973- (Cambridge : Cambridge University Press, 2014)
The development of the Minimalist Program (MP), Noam Chomsky's most recent generative model of linguistics, has been highly influential over the last twenty years. It has had significant implications not only for the conduct of linguistic analysis itself, but also for our understanding of the status of linguistics as a science. The reflections and analyses in this book contain insights into the strengths and the weaknesses of the MP. Among these are, a clarification of the content of the Strong Minimalist Thesis (SMT); a synthesis of Chomsky's linguistic and interdisciplinary discourses; and an analysis of the notion of optimal computation from conceptual, empirical and philosophical perspectives. This book will encourage graduate students and researchers in linguistics to reflect on the foundations of their discipline, and the interdisciplinary nature of the topics explored will appeal to those studying biolinguistics, neurolinguistics, the philosophy of language and other related disciplines.
Machine generated contents note: 1. Introduction; 2. The minimalist programme; 3. The strong minimalist thesis (SMT); 4. The SMT in an evolutionary context; 5. The SMT as an explanatory thesis; 6. Optimal computation and multiple realisation; 7. Conclusion.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Minimalist theory (Linguistics); Biolinguistics; Generative grammar